Escape from HorrorLand - Stine, R. L. (New York : Scholastic, 2009)
Lizzy and Luke are determined to find out what is luring kids to the creepy amusement park and trapping them there.
Escape from HorrorLand -- Enter HorrorLand -- Fear file.
3.7
5-8
Keywords: Amusement parks -- Juvenile fiction; Amusement parks -- Fiction; Horror stories; Amusement parks -- Fiction; Horror fiction; Horror fiction